2016
DOI: 10.1089/cap.2015.0243
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Symptom Improvement Following Stimulant Treatment in Adults with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: The purposes of this study were to examine the impact of 3 weeks of amphetamine administration on intrinsic connectome-wide connectivity patterns in adults with attention-deficit/hyperactivity disorder (ADHD) and explore the association between stimulant-induced symptom improvement and functional connectivity alteration. Methods: Participants included 19 adults (age 20-55 years) diagnosed with ADHD using the Diagnostic and Statistical Manual of Mental Disorders, 4th ed., Text Revision (DSM-IV-TR) cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The results are also in line with recent resting-state studies examining SN abnormality in patients with ADHD ( 16 , 72 ). Another study found that the improvement of ADHD symptom improvement in adults with ADHD by taking in amphetamine was linked to altered insula-medial prefrontal cortex (a core part of DMN) connectivity ( 73 ). These consistent results may suggest that the abnormal salience stimuli allocation procedure mediated by the AI, might be involved in the cognitive and EFs.…”
Section: Discussionmentioning
confidence: 99%
“…The results are also in line with recent resting-state studies examining SN abnormality in patients with ADHD ( 16 , 72 ). Another study found that the improvement of ADHD symptom improvement in adults with ADHD by taking in amphetamine was linked to altered insula-medial prefrontal cortex (a core part of DMN) connectivity ( 73 ). These consistent results may suggest that the abnormal salience stimuli allocation procedure mediated by the AI, might be involved in the cognitive and EFs.…”
Section: Discussionmentioning
confidence: 99%
“…First is that while recruiting from the MTA sample provided a unique and invaluable opportunity to assess brain functional architecture in individuals with childhood ADHD who have been followed longitudinally since middle childhood, our final sample, once divided into 4 groups, was relatively small. Consequently, even though studies have shown that acute (An et al, 2013, Cary et al, 2016, Hong et al, 2015, Yang et al, 2016) and long-term (Battel et al, 2016) stimulant treatment can alter network functional connectivity in ADHD, we were unable to leverage the rich longitudinal phenotypic data available for MTA participants (e.g., treatment received, symptom trajectories) due to the prohibitively small samples remaining once participants were stratified accordingly. Future analyses of data collected as part of the larger MTA study will examine important questions related to the effects of cumulative exposure to ADHD medications over time on neurocognitive performance and brain function; unfortunately such questions could not be addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-brain analyses using MDMR have been used in different cohorts including pediatric samples (72), individuals with Attention Deficit/Hyperactivity Disorder (40, 73), cohorts with psychosis-spectrum symptoms (35) as well as depression and post-traumatic stress disorder (74). Compared to classic seed-based analyses, MDMR has the advantage of using information from all voxels in order to identify “hot spots” of dysconnectivity.…”
Section: Discussionmentioning
confidence: 99%